PERSEPSI WISATAWAN TERHADAP OBJEK WISATA PULAU BOKORI DI DESA BOKORI KECAMATAN SOROPIA KABUPATEN KONAWE - Rahmat, Rahmat (Jurnal Penelitian Pendidikan Geografi, 2018)
This study aims to determine the Tourist Perception of Bokori Island Tourism Object in Bokori Village, Soropia District of Konawe Regency. This study used descriptive qualitative method. Subjects in this study were tourists visiting attractions Bokori Island. Traveler sampling in this study set out in the quota sampling 50 respondents, in this study the sample collection technique by accidental sampling.Methods of  data collection using questionnaires, observation and documentation. Questionnaire data analysis in this research is the analysis presented in the table percentage and distribution. Based on the results obtained show that, according to the perception of tourists attractions of the Bokori Island (1) appeal to the average score - average rating of 3.31 with the perception of being in either category, (2) accessibility with a mean score - average of 3.40 with the perception of tourists are in good category, (3) visitor facilities with a mean score - average rating of 3.12 with the perception of being in either category, (4) infrastructure with a mean score - average 3.53 with the perception of tourists were in the excellent category, (5) security with a mean score - average of 3.24 with the perceptions of visitors are in good category, (6) the promotion with a mean score - average of 3.32 with the perceptions of visitors are in either category. Thus the perception of the overall rating showed a mean score - average rating of 3.32 with the perception of being in either category.